The business value and influence of UX and UI principles in e-commerce - Nekhymchuk, Valeriya (2020)
This bachelor thesis explores the importance of User Experience and User interface principles to an E-commerce website and the value their application contributes to the business. The fields of User Experience and User Interface design were defined and various principles presented. Furthermore, the topic of e-commerce was described with a particular focus on how an e-commerce website's business performance is measured. The reader can expect to be familiarized with the terminology of the topic. The goal is to evaluate the impact of User Experience and User Interface principles on an e-commerce website. It was achieved by surveying people with experience in online shopping and experts in the field of e-commerce. Further insights on the topic were gathered by interviewing some of the expert participants. The results demonstrate that User Experience and User Interface principles are highly valued both by experts who design and optimize e-commerce websites, and the shoppers who use them. The e-commerce professionals who were interviewed also agreed that User Experience and User Interface design bring value to an e-commerce business, and recommended close collaboration between experts in design, sales and data analysis.